Tipologija narečnih glagolskih oblik na primeru govora Ložnice pri Žalcu - Jakop, Tjaša (Slavistična revija, 2003)
The article presents the morphological and accentological characteristics of the local dialect of Ložnica pri Žalcu (Slovenski lingvistični atlas, point 324), which belongs to the dialect of the Central Savinja dialect in the Styrian dialectal group. The verb was analyzed using the methodology for the contemporary analysis of Standard Slovene morphology and morphonology. The typology of verbal forms is presented in the tables of conjugations by accentual types.
Keywords: dialectology; dialektologija; glagol; Ložnica pri Žalcu; oblikoslovje; Slovene; Slovene dialects; slovenska narečja; slovenščina; verb